2001
DOI: 10.1053/jlts.2001.20774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early arterialization of the porcine liver allograft on reperfusion injury, hepatocellular injury, and endothelial cell dysfunction

Abstract: The conventional technique of liver transplantation involves the initial perfusion of the graft with portal blood. However, recent evidence suggests that initial arterialization of the graft may be better. The aim of this study is to evaluate the timing of arterialization on reperfusion injury, hepatocellular injury, and endothelial cell function after liver transplantation. Large white X Landrace pigs (n ‫؍‬ 24) were subjected to orthotopic liver transplantation. The animals were randomly assigned to 4 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…Investigating primary arterial reperfusion experimental and clinical results showed beneficial effects for this method 18, 21–23. This beneficial effect could not be demonstrated in the presented study.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Investigating primary arterial reperfusion experimental and clinical results showed beneficial effects for this method 18, 21–23. This beneficial effect could not be demonstrated in the presented study.…”
Section: Discussioncontrasting
confidence: 58%
“…In experimental studies simultaneous reperfusion showed better microcirculatory perfusion patterns 7. Early arterialization including simultaneous reperfusion was associated with a lower serum aminotransferase peak and a better endothelial function 18. Physiological, simultaneous reperfusion in liver transplantation might provide some potential advantages.…”
Section: Discussionmentioning
confidence: 98%
“…Various reperfusion protocols have been analyzed in 3 experimental studies, using different animal models 1–3. Hickman and Innes1 compared 2 sequential protocols in pigs: initial arterial revascularization (IAR) vs. initial portal revascularization (IPR).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…However, there were no differences in posttransplantation aspartate aminotransferase serum levels among the 2 groups. van As et al2 analyzed 3 different sequences of graft reperfusion in a pig model: IAR, IPR, and simultaneous portal and arterial revascularization. In their study, IAR was associated with less hepatocellular reperfusion injury and better endothelial cell function, when compared to IPR or simultaneous reperfusion.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Our method of arterial reconstruction allows us to reduce the time of arterial revascularizazion of the graft, up to 5-8 min. Early arterial vascularization (12,13) is important for early graft reperfusion and microsurgical technique is a time consuming procedure requiring a reported average reconstruction time of 45-50 min (3).…”
Section: Discussionmentioning
confidence: 99%